Service-oriented education through serviam values: perspectives of school leaders at Santa Ursula Bandung - Carolus Borromeus Mulyatno; Agustinus Tri Edy Warsono (Indonesian Journal of Community Services, 2026)
This qualitative research aims to explore the perceptions of the headteachers of the Santa Ursula schools in Bandung regarding the importance of embodying the ‘serviam’ values of love and compassion, integrity, resilience, unity, total commitment, and service in the process of character education and the development of pupils’ social engagement. This study employed a qualitative approach, utilizing focus group discussions (FGDs) as the data collection technique, involving nine participants from the leadership of the Santa Ursula schools in Bandung. The data from the discussions were analyzed thematically and grouped into five variables, namely (1) value-based planning and assessment, (2) teachers’ role modelling and professional development, (3) collaboration between teachers, pupils and parents, (4) the implementation of meaningful learning, and (5) continuous monitoring, evaluation and reflection. The research findings indicate that the embodiment of ‘serviam’ values in education requires strong institutional cultural support, the role of teachers as role models and pedagogues, synergistic collaboration between the school and families, and a system of continuous evaluation. Teachers act as facilitators and pedagogues who help pupils develop empathy, solidarity, and social responsibility from an early age, in line with the principles of servant leadership. This research recommends that schools strengthen collaboration amongst teachers and with external networks to build a positive performance culture, whilst fostering a concern for service.